2006
DOI: 10.1179/174329006x111519
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysics characteristics and densification of powder metallurgy composites

Abstract: An analytical densification model describing the final stages of hot pressing and sintering has been developed and found to be consistent with empirical findings. The behaviour of composite powders for the matrices of diamond tools has been studied under hot pressing conditions. Differential scanning calorimetry was used to determine the heat capacity at constant pressure C p of pure Co, 663Cu, and composite iron-and cobalt based powders (also containing WC, Ni and 663Cu). The relationship between C p and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…When single DLC coating spinning rings are used in machine for 9 months in a row, the surface of some single DLC coating spinning rings will be damaged. In vie of this, surface treatment process of single DLC coating spinning rings is improved [2][3][4].…”
Section: Transforming Single Dlc Coating Into Ti-dlc Composite Coatingmentioning
confidence: 99%
“…When single DLC coating spinning rings are used in machine for 9 months in a row, the surface of some single DLC coating spinning rings will be damaged. In vie of this, surface treatment process of single DLC coating spinning rings is improved [2][3][4].…”
Section: Transforming Single Dlc Coating Into Ti-dlc Composite Coatingmentioning
confidence: 99%
“…In complete eutectoid composition area, the temperature partition area from P 1 S 1 S 3 curve to P 2 S 2 S 4 curve is defined as complete eutectoid composition reaction area in this paper and the eutectoid reaction temperature partition area , in the left area of vertical lines of eutectoid composition 0.6%C ( or 0.53%C) as well as in the right area of vertical lines of eutectoid composition 0.8%C ( or 0.87%C) with the the temperature partition area from P 1 S 1 S 3 curve to P 2 S 2 S 4 curve are defined as incomplete eutectoid composition reaction area in this paper. Because space limited ,the test inspection is ommitted [1][2][3][4]…”
Section: ⅳ ⅳ ⅳ ⅳ Changes Of Eutectoid Compositionmentioning
confidence: 99%
“…The study involved hot-pressed agglomeration processing of diamond tool (matrix) composites with the rare earth by the doping method, the related service performance tests, and compared the test results for diamond tool (matrix) composites with the rare earth with those for composites free of the rare earth. The results have shown that the service performance of the Fe-based diamond tool (matrix) composites with the rare earth is obviously higher than that of the Febased diamond tool (matrix) composites free of rare-earth doping, the repeatability and stability of the experiment have reached a higher level [1,2].…”
Section: Improvement Of Doping Techniquementioning
confidence: 99%
“…Taken together, these components constitute the most common matrix formulation of hotpressed diamond tool composites. This reseach has mainly involved the preparation of Fe-based bonded powder doped with rare-earth cerium as an important point [1,2], the study of doping rare-earth cerium and the replacement of the expensive Cobased bonded powder in the above matrix formulation. Since the amount of the rare-earth additive is quite small, generally below 1 % of the gross amount of a binding agent, the cost of Fe-based diamond tool composites with the rare earth is very low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation